Measurement of the high-temperature strain of UHTC materials using chemical composition gratings. (30th March 2016) - Xie, Weihua; Meng, Songhe; Jin, Hua; Du, Chong; Wang, Libin; Peng, Tao; Scarpa, F; Huo, Shiyu
Abstract: This paper proposes a simple bonding and measuring technique to realise silica-based chemical composition gratings' (CCGs) high temperature applications on hot structures. We describe a series of experiments on CCGs to measure the thermal and mechanical response characteristics of ultra-high temperature ceramic (UHTC) materials when the maximum temperature is above 1000 °C. Response characteristics are obtained at the heating and cooling stages. Results show that the wavelength response of the CCGs bonded on the UHTC plate increases non-linearly with increasing temperatures, but decreases almost linearly with decreasing temperatures. The temperature-dependent strain transfer coefficients are calculated theoretically and experimentally; results show that the values of strain transfer coefficients below 1000 °C are significantly affected by the thermal expansion coefficient of the substrate material and the interface. The strain transfer coefficient value tends to vary slowly between 0.616 and 0.626 above 700 °C.